Nothingness at the Crossroads of Minor Canons - Selusi Ambrogio (Asian Studies)
It is a mainstream assumption that Asian thinkers, and Chinese in particular, have devoted much of their speculative energies to investigating emptiness and nothingness, whereas these philosophical concepts would have been neglected (if not abhorred) in Western thought. As Sorensen (2022, 77) says: “Having climbed to the precipice of being, the Chinese and Indians pan across the vista of nothingness. They see an open horizon of opportunity. The Greeks look down the cliff. They suffer vertigo”. In this article, we set ourselves the task of questioning this assumption by presenting two authors who represent opposing tendencies within their respective traditions. On the one hand, Wang Fuzhi 王夫之 (1619–1692), normally described as a “materialist” and a bitter opponent of the “emptiness” and “nothingness” of Buddhists and Daoists. On the other, Charles de Bovelles (1479–1566), author of the short treatise Liber de Nihilo, in which nothingness is posited as necessary to God for his existence and the unfolding of his power. Despite being in different traditions and with different visions of nothingness, we will see how their respective thoughts can meet and engage in dialogue in a productive manner.